Hemizygous nonsense variant in the moesin gene (MSN) leads to a new autoimmune phenotype of Immunodeficiency 50 - Kovács, András L.; Kárteszi, Judit; Prohászka, Zoltán; Kalmár, Tibor; Késmárky, Gábor; Koltai, Katalin; Nagy, Zsuzsanna; Sebők, Judit; Vas, Tibor; Molnár, Krisztián; Berki, Tímea; Böröcz, Katalin; et al. (Frontiers in Immunology, 2022)
Here, we present the findings of an investigation involving two male siblings with juvenile total tooth loss, early-onset chronic leg ulcers, and autoimmune thyroiditis, as well as focal segmental glomerulosclerosis with associated pulmonary emphysema in one and diabetes mellitus in the other. The clinical picture and lupus anticoagulant, cryoglobulin, and cold agglutinin positivity suggested the diagnosis of antiphospholipid syndrome. Flow cytometry analysis showed immunophenotypes consistent with immune dysregulation: a low number of naive T cells, elevated CD4+ T cell counts, and decreased CD8+ T-cell counts were detected, and more than half of the T-helper population was activated. Considering the siblings’ almost identical clinical phenotype, the genetic alteration was suspected in the background of the immunodeficiency. Whole exome sequencing identified a previously not described hemizygous nonsense variant (c.650G>A, p.W217X) within exon 6 of the moesin (MSN) gene localized on chromosome X, resulting in significantly decreased MSN mRNA expression compared to healthy controls. We present a putative new autoimmune phenotype of Immunodeficiency 50 (MIM300988) characterized by antiphospholipid syndrome, Hashimoto’s thyroiditis, leg ulcers, and juvenile tooth loss, associated with W217X mutation of the MSN gene.